Pembelajaran Kesenian Guritan Menggunakan Metode Demonstrasi Di Kelas Iv Sd Negeri 7 Mulak Ulu Kabupaten Lahat - Ova; Feri Firmansyah; Muhsin Ilhaq (Lembaga Pengembangan Kinerja Dosen, 2024)
Arts and culture subjects play an important role in shaping students into creative individuals, maintaining and developing the nation's cultural heritage, while providing support in facing future challenges. The skills acquired through this subject are considered an integral part of the provision provided to students. In the current era, it can be seen that cultural heritage is increasingly fading because it is being eroded by time. Cultural performances and the number of traditional art performers continue to decline, especially guritan art, which has resulted in this cultural heritage becoming increasingly unknown to the public, and people's interest in enjoying traditional art performances from their ancestors is also decreasing. This condition is a serious concern for South Sumatra cultural observer, Vebri Alianti, who stated that cultural heritage is currently threatened with extinction and being eroded by the currents of time (Faldy, 2018). Guritan lahat often highlights local stories, regional legends, heroic stories, as well as the values ​​of introducing and providing an understanding of the art of guritan in class IV of SD Negeri 7 Mulak Ulu, Lahat Regency using the demonstration method. Through this assessment, it is hoped that it can contribute to the development of arts education in Lahat in particular and in Indonesia in general. Thus, this research is entitled